Adverse impacts of agricultural expansion on hydrological and nutrient dynamics in a Renosterveld landscape – can natural vegetation offer solutions - De Waal, Jan (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.